PHYTOSANITARY STATE OF PLANTS THE GENUS BETULA IN THE BOTANICAL GARDEN ZhNAEU - M. Shvets; F. Markov; E. Galev; A. Pitsil; I. Kulbanska (Наукові горизонти, 2020)
Objective – to assess and analyze the phytosanitary condition of plants of the genus Betula on the territory of the botanical garden of the Zhytomyr National Agroecological University. In the course of the research, the following methods were used: route-visual, forestry-inventory, mycological, phytopathological, and comparatively calculated. Diagnosing the viability of forest plants, we used visual and instrumental approaches. The condition of plant specimens was evaluated in three categories: good, satisfactory, and unsatisfactory. Materials were processed using the Microsoft Office Word and Microsoft Office Excel computer programs. The phytosanitary condition of plants from the genus Betula was assessed and analyzed on the territory of the botanical garden of the Zhytomyr National Agroecological University. In the territory of the botanical garden, specimens of Betula raddeana Traut., B. lenta L., B. papyrifera Marsh., B. schmidtii Reg., B. dahurica Pall. are in excellent physiological condition now. Somewhat weakened infectious pathologies are B. pendula Roth. and B. pubescens Ehrh. Diagnosed their pathological processes with the identification of the species composition of pathogens of infectious diseases and pathologies of non-infectious nature. In general, the phytosanitary condition of the studied specimens is satisfactory; however, 27.3 % of plants of Betula are now weakened. Infectious diseases of birch trees of various etiologies have been identified. Brown spots are the most common among diseases of fungal etiology - the pathogen Marssonina betulae. Diagnosed the presence of wood destroyers Fomitopsis betulina and Fomes fomentarius. Found diffuse foci of half-parasite mistletoe white (Viscum album). Among the bacterioses, the negative effect of the pathogens of the bacterial burn of (Erwinia amylоvora) and the bacterial dropsy of silver birch (Lelliottia nimipressuralis) on the morphological and physiological state of plants has been established. In shape of the bark, silver birch with a rhomboid-fissured form of the bark turned out to be resistant to bacterial dropsy, the least stable with a smooth shape. On the examined tree trunks, the pattern of altitude of ulcers from dropsy (as integral components of the symptoms of bacteriosis) was revealed, where they were noted up to a height of 15.5 m. A key step in the development plant of Betula health measures is environmental and pathological monitoring, annual sanitary trimming of affected shoots and dry branches, and the use of biological products based on aerobic spore-forming bacteria Bacillus sp.